Do Managers Give Hometown Labor an Edge? - Yonker, Scott E. (Review of Financial Studies, 2017)
In line with the psychological theory of place attachments, managers favor hometown workers over others. Consistent with this prediction, I find that following periods of industry distress, establishments located near CEOs’childhood homes experience fewer employment and pay reductions and are less likely to be divested relative to other firm establishments. While it is not possible to directly test whether this employment bias destroys firm value, managers only implement these policies when governance is weak, suggesting that this favoritism is suboptimal. Together, these results provide direct evidence of employee favoritism and show that idiosyncratic manager styles impact corporate employment decisions.